Rancang Bangun Aplikasi Reminder Service Untuk Kenaikan Pangkat Dan Informasi Pensiun ASN Menggunakan Whatsapp Api Berbasis Website - Habib Al Qadri; Al-Khowarizmi Al-Khowarizmi; Septiana Dewi Andriana (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
This research aims to design and develop a web-based reminder service application that informs Civil Servants (ASN) about promotions and retirement information through the WhatsApp API. Currently, notifications regarding promotions and retirement information for ASN are still manually conveyed through WhatsApp messages without standardization. This research aims to provide more structured information about promotions and retirement, from scheduling to standardized messages. The research focuses on the need for an efficient system to manage and deliver important information related to ASN promotions and retirement, given the frequent delays and inaccuracies in information dissemination. The system development method used is the Waterfall model, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. This application is built using the PHP programming language and the Yii Framework, and it integrates the WhatsApp API for personal notifications. Testing results show that this application functions well, providing timely notifications and making it easier for ASN to receive important information related to promotions and retirement through WhatsApp. The web-based reminder service application with WhatsApp API integration is effective in enhancing the efficiency of delivering promotion and retirement information to ASN and is expected to be widely implemented in personnel administration systems.